The Gift of Necessity, A Case Study of Lecturers’ Use of Webinars - Mani Festati Broto; Widyasari (Universitas Terbuka, 2021)
This started as a brief and simple survey aimed to measure the extent to which university lecturers were compelled to attend webinars after the WfH policy was in place, in terms of motivation, challenges and benefits of webinar attendance. The survey also tried to see how instructors would one of their duties under the University Instructors’ Three Principles, i.e. active engagement in online seminars (webinars). It applies the descriptive qualitative approach to identifying how they understand the aspect of social interaction. This study focuses on how instructors make use of webinar technology out of necessity that later proved, time-wise, to be more effective and efficient in organization. ‘Time’ can be managed in the most efficient way possible, and turns out to be a gift, in that it facilitates the enhancement of knowledge. However, webinars still cannot be substitutes for the sorely-missed social interactions. Dimulai sebagai survei singkat dan sederhana yang bertujuan untuk mengukur sejauh mana dosen universitas didorong untuk menghadiri webinar setelah kebijakan WFH diberlakukan, dalam hal motivasi, tantangan, dan manfaat dari kehadiran webinar. Survei ini juga mencoba melihat bagaimana instruktur menjalankan salah satu tugasnya di bawah Tiga Prinsip Instruktur Universitas, yaitu keterlibatan aktif dalam seminar online (webinar). Penelitian ini menerapkan pendekatan kualitatif deskriptif untuk mengidentifikasi bagaimana mereka memahami aspek interaksi sosial. Penelitian ini berfokus pada bagaimana instruktur memanfaatkan teknologi webinar karena kebutuhan yang kemudian terbukti, dari waktu ke waktu, lebih efektif dan efisien dalam organisasi. ‘Waktu’ dapat dikelola dengan cara yang seefisien mungkin, dan ternyata menjadi anugerah, dalam hal memfasilitasi peningkatan pengetahuan. Namun, webinar tetap tidak bisa menggantikan interaksi sosial yang sangat dirindukan.